Enhancing feedback quality through eye-tracking systems in teaching practice - Kleiner, K. N. (2017)
In the field of teacher education practical school training, in classes of an experienced teacher, are the dominant form of didactical learning. Due to contentual and organizational reasons it is going to be discussed how video footage could improve the professionalization of students. Further development and alternative concepts to improve the feedback quality for students, in practical school training, are given with the use of Eye-tracking systems. In the remaining explanations a study concerning the feedback quality at work with students of physical education is represented and the advantages of Eye-tracking in teacher education are discussed. Eye-tracking systems have been used in various fields, measuring people`s viewing behaviour. We demonstrate the usefulness of eye-tracking by exploring the ability to discern import from unimportant incidents in motoric learning sequences and complex teaching situations, as well as the ability to decide where to direct one`s attention. Eye-tracking systems have been used in various fields (e.g. research of perception, cognition, marketing, usability), measuring people`s viewing behaviour. Likewise, eye-tracking systems have been applied in various sports (e.g. cricket, table tennis, ice speed skating, basketball, handball, volleyball, shooting, Formula 1, gymnastics). One of the most important factors measured by eye-tracking systems is the scan path, indicating the order and time-frame of perceived pieces of information. Such data can be analyzed to investigate and compare the scan paths of e.g. experts and novices.